1991
DOI: 10.5547/issn0195-6574-ej-vol12-no1-7
|View full text |Cite
|
Sign up to set email alerts
|

Cutting CO2 Emissions: The Effects of Alternative Policy Approaches*

Abstract: This paper starts from the premise that attempts to curtail global emissions of greenhouse gases are likely to be made in the next few decades. We discuss some of the possible international effects which could result from attempts to achieve such a cutback, and illustrate a methodology which we hope to extend, in subsequent work, to further evaluating the consequences of responding to the problem of global warming. We identify possible magnitudes of effects of cutting global C02 emissions, and illustrate ways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(24 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…For example, if the only alternative to regulation at the point of extraction was regulation farther downstream (e.g., carbon-linked tariffs) (http://krugman.blogs.nytimes.com/ 2009/06/29/climate-trade-obama/), extracting countries might lose not just the value of their fossil resources but also the revenues that could be generated from taxes collected or permits sold (17). Indeed, at least one study has concluded that substantial reductions in emissions could be realized with near term gains in the GDP of oil-producing countries in the Middle East (18). Emissions instead regulated at the point of import, combustion, or consumption of goods would generate revenues in the country where the fuels are burned or goods are consumed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, if the only alternative to regulation at the point of extraction was regulation farther downstream (e.g., carbon-linked tariffs) (http://krugman.blogs.nytimes.com/ 2009/06/29/climate-trade-obama/), extracting countries might lose not just the value of their fossil resources but also the revenues that could be generated from taxes collected or permits sold (17). Indeed, at least one study has concluded that substantial reductions in emissions could be realized with near term gains in the GDP of oil-producing countries in the Middle East (18). Emissions instead regulated at the point of import, combustion, or consumption of goods would generate revenues in the country where the fuels are burned or goods are consumed.…”
Section: Discussionmentioning
confidence: 99%
“…5 Also, the possible advantages of the adoption of extraction-based accounting 2 and policies 68 have been explored. In the short term, however, international agreement on a switch in the target base appears unlikely.…”
Section: Switching the Internationally Agreed Target Basementioning
confidence: 99%
“…In the early 1990s, several studies used these models to assess the effects of policies which reduce CO 2 emissions. The work of Wigle (1991a and1991b) and Pezzey (1992) in this direction should be noted. These models are dynamic and focus Despite the recognized advantages of all these models, they can be criticized in several regards.…”
Section: Cge Applications For Analysis Of Environmental Policiesmentioning
confidence: 99%